PERBEDAAN KEMAMPUAN REPRESENTASI KOMUNIKASI DAN MATEMATIS MODEL TTW DAN TAI - Indah Lestari; Indra Jaya; Isran Rasyid Karo-Karo (Relevan : Jurnal Pendidikan Matematika, 2022)
Penelitian ini bertujuan untuk mengetahui perbedaan kemampuan representasi dan komunikasi matematis siswa yang diajar menggunakan model pembelajaran think talk write dan model pembelajaran TAI. Jenis penelitian ini adalah Eksperimen Semu. Populasi dalam penelitian ini adalah seluruh siswa MAS Pondok Pesantren Darul Qur’an T.P 2020−2021. Sampel dalam penelitian ini adalah kelas X MIA 1 sebagai kelas yang diajar menggunakan model pembelajaran think talk write dan kelas X MIA 2 sebagai kelas yang diajar menggunakan model pembelajaran team assisted individualization. Data diperoleh dari post-test dengan 5 butir soal tes kemampuan representasi dan 5 butir soal tes kemampuan komunikasi. Data dianalisis secara deskriptif dan menggunakan teknik Two Way ANAVA dan dilanjutkan dengan uji Tukey. Berdasarkan hasil analisis data dan pembahasan, diperoleh: 1) Kemampuan representasi matematis siswa yang diajar menggunakan model pembelajaran think talk write tidak lebih baik daripada siswa yang diajar menggunakan model pembelajaran team assisted individualization; 2) Kemampuan komunikasi matematis siswa yang diajar menggunakan model pembelajaran think talk write lebih baik daripada siswa yang diajar menggunakan model pembelajaran team assisted individualization; 3) Kemampuan representasi dan komunikasi matematis siswa yang diajar menggunakan model pembelajaran think talk write lebih baik daripada siswa yang diajar menggunakan model pembelajaran team assisted individualization. ABSTRACT This study aims to determine the differences in mathematical representation and communication skills of students who are taught using the think talk write learning model and TAI learning model. This type of search is a quasi-experimental. The population in this study were all high school students of Darul Qur’an Islamic Boarding School in the academic year 2020−2021. The sample in this study was class X mathematics science 1 as a class taught using the think talk write learning model and class X mathematics science 2 as a class taught using a team assisted individualization learning model. The data was obtained from the posttest with 5 items for the representation ability test and 5 items for thecommunication ability test. The data were analyzed descriptively and using the Two Way ANAVA technique and continued with the Tukey test. Based on the results of data analysis and discussion obtained: 1) The mathematical representation ability of students who were taught using the think talk write learning model is not better than students who are taught using the team assisted individualization learning model; 2) The mathematical communication skills of students who are taught using the think talk write learning model are better than students who are taught using the team assisted individualization learningmodel; 3) The mathematical representation and communication skills of students who are taught using the think talk write learning model are better than students who are taught using the team assisted individualization learning model.